Highly Conductive, Air‐Stable Silver Nanowire@Iongel Composite Films toward Flexible Transparent Electrodes. Issue 33 (14th June 2016) - Xiong, Weiwei; Liu, Hongliang; Chen, Yongzhen; Zheng, Meiling; Zhao, Yuanyuan; Kong, Xiangbin; Wang, Ying; Zhang, Xiqi; Kong, Xiangyu; Wang, Pengfei; Jiang, Lei
Abstract : A new type of flexible transparent electrode is designed, by employing wettability‐induced selective electroless‐welding of silver nanowire (AgNW) networks, together with a thin conductive iongel as the protective layer. The obtained electrode exhibits high optical transmittance, and excellent air‐stability without sacrificing conductivity.